Campbell's operative orthopaedics - Campbell, Willis C. (Willis Cohoon), 1880-1941.; Canale, S. T. (S. Terry); Beaty, James H. (Philadelphia, PA : Mosby/Elsevier, 2008)
The most trusted and widely used resource in orthopedic surgery in an all-new four-color design, providing exceptional visual guidance on more than 1,800 operative and minimally invasive procedures. Totally revised and updated, it encompasses all of the very latest procedures, techniques, and instruments. Drs. S. Terry Canale and James H. Beaty along with 22 other authorities from the Campbell Clinic present encyclopedic, in-depth coverage of the field, organized for efficient access.
V.4 Peripheral nerve injuries. Peripheral nerve injuries / Mark T. Jobe, Santos F. Martinez -- Microsurgery. Microsurgery / Mark T. Jobe -- Hand. Basic surgical technique and aftercare ; Acute hand injuries ; Flexor and extensor tendon injuries / Phillip E. Wright II -- Fractures, dislocations, and ligamentous injuries / James H. Calandruccio, Mark T. Jobe -- Nerve injuries / Mark T. Jobe -- Wrist disorders ; Special hand disorders / Phillip E. Wright II -- Paralytic hand / James H. Calandruccio, Mark T. Jobe -- Cerebral palsy of the hand / Mark T. Jobe -- Arthritic hand / Phillip E. Wright II -- Compartment syndromes and volkmann contracture / Mark T. Jobe -- Dupuytren contracture / James H. Calandruccio -- Carpal tunnel, ulnar tunnel, and stenosing tenosynovitis / Phillip E. Wright II -- Tumors and tumorous conditions of the hand / James H. Calandruccio, Mark T. Jobe -- Hand infections / Phillip E. Wright II -- Congenital anomalies of the hand / Mark T. Jobe -- Foot and ankle. Surgical techniques ; Disorders of the hallux / E. Greer Richardson -- Pes planus / G. Andrew Murphy -- Lesser toe abnormalities / Susan N. Ishikawa, G. Andrew Murphy -- Rheumatoid foot / David R. Richardson -- Diabetic foot / Susan N. Ishikawa -- Neurogenic disorders ; Disorders of nails and skin / E. Greer Richardson -- Disorders of tendons and fascia ; Fractures and dislocations of the foot / G. Andrew Murphy.
Includes bibliographical references and index.
Keywords: Orthopedic surgery; Orthopedic Procedures